1993
DOI: 10.1177/000348949310200702
|View full text |Cite
|
Sign up to set email alerts
|

Transient Hypocalcemia after Thyroidectomy

Abstract: The causes of transient hypocalcemia after thyroid surgery are not fully understood. In 95 consecutive patients undergoing total thyroidectomy (n = 30), subtotal thyroidectomy (n = 14), or hemithyroidectomy (n = 51), we serially measured total calcium, parathyroid hormone (PTH), and proteins before surgery and 6, 24, 48, 72, and 96 hours after surgery, and we calculated the corresponding ionized calcium levels. In the whole population, there was a statistically significant decrease of PTH, total calcium, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
81
0
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 15 publications
3
81
0
6
Order By: Relevance
“…Transient hypocalcemia has been described in over 65% of cases, while permanent post surgical hypocalcemia is thought to occur in up to 10 % of cases [1][2][3][4][5][6][7][8][9]. Mild postoperative hypocalcemia may be asymptomatic.…”
Section: Introductionmentioning
confidence: 99%
“…Transient hypocalcemia has been described in over 65% of cases, while permanent post surgical hypocalcemia is thought to occur in up to 10 % of cases [1][2][3][4][5][6][7][8][9]. Mild postoperative hypocalcemia may be asymptomatic.…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous muscle cramps are commonly seen in hypocalcemia. Prolonged contraction of the respiratory and laryngeal muscles causes stridorous breathing and can cause cyanosis [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…In this series parathyroid insufficiency was observed in 52 (8.69%) patients, and only one patient (0.16%) among them developed permanent parathyroid insufficiency. Several studies reported an incidence of 5% to 30% of postoperative hypocalcaemia in thyroidectomized patients 7,12,13 . Incidence of parathyroid insufficiency was higher in bilateral procedures in comparison to unilateral ones (9.52% vs 5.21%) in this series.…”
Section: Discussionmentioning
confidence: 99%